EEG Characteristics of Dementia With Lewy Bodies, Alzheimer’s Disease and Mixed Pathology - van der Zande, Jessica J.; Gouw, Alida A.; van Steenoven, Inger; Scheltens, Philip; Stam, Cornelis Jan; Lemstra, Afina W. (Frontiers in Aging Neuroscience, 2018)
Introduction Previous studies on electroencephalography (EEG) to discriminate between dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD) have been promising. These studies did not consider the pathological overlap of the two diseases. DLB-patients with concomitant AD pathology (DLB/AD+) have a more severe disease manifestation. The EEG may also be influenced by a synergistic effect of the 2 pathologies. We aimed to compare EEG characteristics between DLB/AD+, ‘pure’ DLB (DLB/AD-), and AD. Methods We selected probable DLB patients who had an EEG and cerebrospinal fluid (CSF) available, from the Amsterdam Dementia Cohort. Concomitant AD-pathology was defined as a CSF tau/Aβ-42 ratio>0.52. 41 DLB/AD+ cases were matched for age (mean 70(range 53-85) and sex (85% male) 1:1 to DLB/AD- and AD-patients. EEGs were assessed visually, with Fast Fourier Transform, network- and connectivity measures. Results EEG visual severity score (range 1-5) did not differ between DLB/AD- and DLB/AD+ (2.7 in both groups) and was higher compared to AD (1.9, p <0.01). Both DLB groups had a lower peak frequency (7.0 and 6.9 Hz in DLB vs. 8.2 in AD, p<0.05), more slow-wave activity and more prominent disruptions of connectivity and networks, compared to AD. No significant differences were found between DLB/AD+ and DLB/AD-. Discussion EEG abnormalities are more pronounced in DLB, regardless of AD co-pathology. This emphasizes the valuable role of EEG in discriminating between DLB and AD. It suggests that EEG slowing in DLB is influenced more by the α-synucleinopathy, or the associated cholinergic deficit, than by amyloid and tau pathology.